Seasonality and trophic diversity in molluscan assemblages from the Bay of Tunis (southern Mediterranean Sea) - ANTIT, M.; DAOULATLI, A.; URRA, J.; RUEDA, J. L.; GOFAS, S.; SALAS, C. (Mediterranean Marine Science, 2016)
Soft bottom molluscan assemblages from the Bay of Tunis have been studied in order to analyse their seasonality and trophic diversity in relation to environmental variables. A total of 147 species of molluscs was identified, with gastropods displaying the highest species richness and bivalves the highest abundances, and including five non-indigenous species such as the dominant ectoparasite Polycerella emertoni. Carnivorous and scavenger gastropods were among the most frequent species, reflecting a diverse benthic community. Seasonal changes were significant, being more acute at 3-4 m than at 10-15 m depth, and were driven mainly by seawater temperature and percentage of organic matter in the sediment. The high affluence of tourists in summer was coincident with high decreases in species richness and abundance of molluscs, together with a strong siltation of the sediment. Nevertheless, most trophic groups remained and the trophic diversity was relatively high. Significant relationships were found between the index of trophic diversity and Shannon-Wiener diversity and evenness indices, suggesting that the identity of the species with its particular trophic trait, together with the good distribution of the individuals among the species (density) would be the drivers for the maintenance of the molluscan food web under environmental stress. The abundance of P. emertoni altered the trophic structure of the molluscan assemblage, with the ectoparasite trophic group reaching an unusual punctual higher dominance. Soft bottom molluscan assemblages of the Bay of Tunis should be taken into account in monitoring programs for anthropogenic impacts and non-indigenous species trends throughout the Mediterranean basin.